Fatal invasive candidiasis in COVID-19 patient with severe bleeding and extensively drug-resistant Klebsiella enterobacter - Tatjana Adzic-Vukicevic; Jelena Velickovic; Aleksandra Radovanovic-Spurnic; Dejan Velickovic; Sara Milenkovic; Filip Petrovic; Jelena Micic; Natasa Dragutinovic (Journal of Infection in Developing Countries)
Introduction: Multi-organ dysfunction caused by thromboembolic complications may complicate the course of SARS-CoV-2 infection. Most patients require anticoagulant therapy which predisposes them to the development of hemorrhagic syndrome. In critically ill COVID-19 patients secondary infections due to opportunistic pathogens are associated with a high mortality rate.